IB - "Hiebert, Ray Eldon.(ed.)" (New York, 1988)
There can be no question that the media play an important role in our contemporary society. This edition of Impact of Mass Media explores the issues surrounding the growing presence of mass media in our everyday lives by presenting arguments from contemporary leading thinkers, observers, and critics. This new edition features thought-provoking, new articles on topics such as diversity in the age of electronic news, global media giants, government secrecy, and the slow death of culture. By providing a balanced approach for examining the effects of media on current issues, Hiebert lets students decide for themselves how mass media can be manipulated and how mass media manipulate the public.
Keywords: Mass Media